Evaluation of brainstem auditory evoked response audiometry findings in children with tuberculous meningitis at admission - Topcu, Ismail; Cüreoğlu, Sebahattin; Yaramiş, Ahmet; Tekin, Muhammet; Oktay, Faruk; Osma, Ustün; Meric, Faruk; Katar, Selahattin (Auris, nasus, larynx, 2002)
Objective: To determine the characteristics of Brainstem auditory evoked response (BAER) findings in children with tuberculous meningitis (TBM) at admission. Methods: Twenty-seven children with highly probable TBM were admitted to the University Hospital. The control group was 23 healthy, age and sex matched subjects. Brainstem response audiometry recording was performed in all patients and controls. Ninety dB sound pressure level (SPL) was used for comparisons. The main BAER measurements analysed were the I–III, III–V, I–V interpeak intervals. In statistical analysis, t-test for independent groups were performed. At the same time, for interpeak intervals, values exceeding 2.5 standard deviations (S.D.) above the means of the normal controls were considered abnormal. To the result of BAER findings, HL was classified as mild (until 40 dBHL), severe (until 80 dBHL) and total HL (no hearing was detected). Results: The latencies of interpeak intervals (except III–V latency at 10 per s) have significantly prolonged in comparison with controls. Mild HL was detected in four ears. In eight ears, any wave form could not be obtained at 110 dBSPL. Abnormal BAER result was seen in 13 of 54 ears (24%) at the click of 10 per s and five ears (12%) at the click of 50 per s. Conclusion: Abnormal BAER result was seen in 24% of patients with TBM before treatment. Depending on these findings, it can be inferred that hearing impairments must be lower than those values which was detected by BAER during the acute phase of TBM, since the abnormal BAER may be reversible following the illness, returning to normal with recovery.